GEOLOGY AND STATIC HYDROCARBON RESERVOIR MODELLING TO ESTIMATE ORIGINAL HYDROCARBON IN-PLACE OF BEKASAP FORMATION, TR FIELD, CENTRAL SUMATRA BASIN - Tambunan, Theresia
TR Field is an oil field in the development stage in Central Sumatra Basin. Geological study and reservoir modelling focus on Bekasap Formation with reservoir interval, consist of sandstone as its lithology. This study conducted to comprehend the geological condition, build reservoir static modelling, and estimate the TR field's hydrocarbon reserve in place. Data used in this research consist of wireline logs from 16 wells, core description, threedimensional seismic data, and well test data. This study's methods comprise sequence stratigraphic analysis, depositional environment analysis, geological structural analysis, reservoir property analysis, three-dimensional structural modelling, facies and petrophysical modelling, determination of fluid contacts, and hydrocarbon reserve estimation. The outcome from all those methods portrays the geological condition of the study area. Bekasap Formation deposited during a regressive phase in delta environment. Geological structure in TR Field consists of northwest-southeast anticline as a result of compressive deformation with northeast-southwest stress direction. This compressive deformation is also suspect to reactivate the northeast-southwest and northwest-southeast normal faults, which formed in wrenching deformation. The hydrocarbon reserve in-place (STOOIP) estimation on three identified blocks gives the total value of 3,21 MMSTB.